The philosophic work of Prof. Milan Komar - Ogrin, Matija (Two Homelands, 2001)
Milan Komar (born in 1921) is a Slovene emigrant philosopher who lives and works since 1948 in Argentina. His research work went from medieval philosophy through Wolff and Kant to Hegl, Marx and to modern phenomenological and existential philosophical streams. He also studied linkages between the discoveries of the antique and medieval philosophy, and those of modern psychological and psychiatric science. Komar had many scholars and successors as his professional work in Argentina was named “Escuola di Komar”.